2000
DOI: 10.1161/01.cir.102.18.2269
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Inhibitor Attenuates Left Ventricular Hypertrophy, Leading to Prevention of Heart Failure in Hypertensive Rats

Abstract: Calcineurin inhibition, if started from the initial stage of pressure overload, attenuated the development of LV hypertrophy without any effect on LV fibrosis and prevented the transition to heart failure. The activation of calcineurin is involved in the development of LV hypertrophy but not of LV fibrosis, and this involvement may be crucial at the initial stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 15 publications
6
47
1
Order By: Relevance
“…The results of the present study support an increasing body of literature consisting of 13 reports at present which demonstrate a partial or complete inhibition of cardiac hypertrophy or heart failure by using cyclosporine and͞or FK506 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(41)(42)(43). However, such reports remain controversial for a number of reasons.…”
Section: Discussionsupporting
confidence: 81%
“…The results of the present study support an increasing body of literature consisting of 13 reports at present which demonstrate a partial or complete inhibition of cardiac hypertrophy or heart failure by using cyclosporine and͞or FK506 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(41)(42)(43). However, such reports remain controversial for a number of reasons.…”
Section: Discussionsupporting
confidence: 81%
“…For example, some reports have indicated that cyclosporine could actually be protective against reperfusion-associated dysrhythmias (16). Other reports have indicated that cyclosporine may also be protective against the development of left ventricular hypertrophy and cardiac enlargement (17), although tacrolimus appears to have at least an equivalent effect (18). Clinically important interactions between cyclosporine and amiodarone, which the present study could not measure, have been reported (19,20).…”
Section: Discussionmentioning
confidence: 66%
“…A number of recent studies have investigated calcineurin activity in various animal models of cardiac hypertrophy (1,16,18,19). Several studies demonstrated an increase in calcineurin activity in pressure-overload hypertrophy (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac hypertrophy is a leading cause of the development of congestive heart failure and sudden death in humans (1).…”
Section: Introductionmentioning
confidence: 99%